Global Research Trends in Quantum Computing: A Scientometric Analysis of 50 Years Using the Dimensions Database - Anbalagan, Muthuraj (Journal of Data Science, Informetrics, and Citation Studies, 2026)
This paper examines global research trends in quantum computing. Quantum computing is a multidisciplinary field that combines elements of mathematics, physics, and computer science. It uses quantum mechanics to solve complicated problems more quickly than traditional computers. Scientometrics is a quantitative and statistical approach that analyses research on specific themes. The study analysed 50 years of quantum computing research from 1977 to 2026. The research publication data were collected from the Dimensions database. The study aims to analyse quantum computing research across the Sustainable Development Goals (SDGs), year-wise distribution of research publications, year-wise distribution of citations, publications with citations by year, year-wise trends of the Field Citation Ratio, year-wise trends of the Relative Citation Ratio (RCR), top ten leading authors, top 25 core source journals, open access publishing patterns, top 25 highly cited research papers, citation analysis networks, and co-authorship analysis networks. The study found that a total of 1,643 quantum computing research publications were published under SDG 9 (Industry, Innovation and Infrastructure), and these publications received the highest number of citations (52,718), with a high mean citation value of 32.09. The majority of 6,773 research papers were published in 2025, receiving 149,986 citations. Zhu Han (University of Houston, United States) has published 179 research publications and received 4,148 citations. The IEEE Access journal has published 1,575 research publications and received 45,857 citations. The article “Computational Thinking,” published in Communications of the ACM (2006), has received 6,006 citations.
Keywords: Citation Analysis; Dimensions Database; Quantum Computing; Research Trends; Scientometric Analysis; Sustainable Development Goals (SDGs)